Role of Limited Endoscopic Sphincterotomy (ES) and Endoscopic Papillary Large-Balloon Dilation (EPLBD) in the Management of Difficult Common Bile Duct Stones: A Single-Center Experience - Tendean, Michael; Mambu, Toar D. B.; Tjandra, Ferdinand; Salem, Billy E. C. R.; Panelewen, Jimmy; Paparang, Steven (Medical Scope Journal, 2025)
Abstract: Difficult common bile duct (CBD) stones provide challenges in their therapeutic management, especially per endoscopic treatment. In this study, the author would like to show the effectiveness of limited ES and EPLBD in the management of patients with difficult CBD stones in their center. This is a retrospective study from June 2020 to April 2024, in which patients with difficult CBD stones received endoscopic management with limited endoscopic sphincterotomy and EPLBD. Length of procedure, success rate, morbidity, and mortality rate were recorded and evaluated. The results showed that a total of 98 patients were included in the study, ages ranging from 23 to 83 y.o. The length of the procedure was 44 + 11 minutes, with the success rate of CBD stone retrieval and duct clearance at 70.4%. Etiologies of difficult CBD stones consist of stone size > 1.5 cm (47.96%), combined cause (27.55%), multiple CBD stones less than 1.5 cm (13.26%), and tapering of distal CBD (11.22%). Morbidities such as melena (5.1%), post-ERCP pancreatitis (PEP) (3.06%), cholangitis (1.02%), and duodenal perforation (1.02%) occurred. One mortality incidence occurred due to severe cholangitis and sepsis. The mean period of EPLBD performed was 2.7 + 1.57 minutes. The pressure strength of the CRE balloon dilator commonly used was 4.5 atm. In conclusion, limited ES and EPLBD offer quite satisfactory results in the management of difficult CBD stones, with the success rate as high as 70.4% and an acceptable morbidity rate. Keywords: endoscopic papillary large-balloon dilation (EPLBD); difficult CBD stones